Pengelolaan Pariwisata Berbasis Digital di Objek Wisata Pantai Minang Rua Kabupaten Lampung Selatan: Studi Kasus Manajemen Destinasi - Indah Sugiarti; Budi Rahman; Hadori Rosadi (Yayasan Literasi Sains Indonesia, 2025)
This study aims to analyze the implementation and potential of digital-based tourism management at the Minang Rua Beach tourist destination in South Lampung. Using a descriptive qualitative approach and case study method, data were collected through in-depth interviews, field observations, and document analysis involving tourism managers, local government, tourism business actors, and visitors. The findings reveal that digital tourism management at Minang Rua Beach is still limited to social media promotion, which is not yet professionally organized. Digital infrastructure, such as internet connectivity, online booking systems, and digital information services, remains underdeveloped. Key challenges include low digital literacy among managers, limited technological resources, and a lack of synergy among stakeholders. Nevertheless, there is great potential to develop digital-based tourism management due to the increasing reliance of tourists on digital information, the emergence of youth-driven digital initiatives, and supportive policies from the central government. This study recommends the development of digital infrastructure, human resource training, and cross-sector collaboration to establish an innovative, efficient, and sustainable tourism management system. The digitalization of tourism management is expected to enhance destination competitiveness and provide a more adaptive visitor experience in the digital era